Older Women and Political Agency: A Scoping Review of the Literature - Nicole Mazzucchelli; Luciana Hedrera; Lupicinio Iñíguez-Rueda; María Isabel Reyes-Espejo (Psykhe, 2024)
Older women’s political agency has not been widely explored in the literature on ageing. In general, this group has been researched from the ageing characteristics perspective—decay, fragility, adaptive processes—or considering those dimensions in which their capacity for agency lessens ageing symptoms. However, the implications and political character of their practices tends to be ignored. This scoping review examines the approaches to older women’s political agency found in the 1975-2020 academic production. We conducted this scoping review according to PRISMA-ScR guidelines and Arksey and O’Malley’s (2005) methodological framework. Sixty-five articles were included in the revision and a full thematic content analysis of the selected corpus was conducted. Qualitative methods were incorporated in 75 % of the examined articles that were conducted in Canada, the United States, and the United Kingdom. Diverse approaches to the topic of political agency were identified with community participation, activism, and trajectories of coping and resilience standing out. The relational and collective character of the processes of agency are paramount in the specific strategies that women develop to face vital transitions. Older women’s political agency takes place in a range of social spaces, having a relevant impact at the social-public and the domestic level. A situated characterization of political agency in older women can help guide and redefine public actions, contributing to a greater recognition of these women’s experiences, actions, and contributions.